Graphical information in corporate annual report: an exploratory survey of user’s perceptions / Rosiatimah Mohd Isa, Hasnah Haron and Sofri Yahya - Mohd Isa, Rosiatimah; Haron, Hasnah (Accounting Research Institute (ARI) & Faculty of Accountancy, 2006)
The graphical presentation of quantitative data within corporate annual reports has become one of the techniques used by management to disclose quantitative information to their users. This survey investigates the perceptions of users of CAR with regard to the graphical information in corporate annual report. Responses from completed questionnaire of a sample of 52 respondents were examined. The users of CAR in the study ranked graphical information of statistical data as second after financial statements. The five most important variables graphs preferred by respondents are sales graph, earnings, EPS, share price and cash flow graph. Graphical disclosure in CAR was considered sufficient by majority of the respondents. However, they were not fully aware of major criteria of good graphical constructions and designs.